Perlindungan Hukum Bagi Peserta Misi Khusus PBB Terkait dengan Kematian dalam Pelaksanaan Tugas (Studi Kasus Pasukan Garuda Lebanon 2022) - Kusuma, Surya; Harisman, Harisman (Universitas Ekasakti, 2024)
In order to protect the rights and obligations of UN special mission participants while they carry out their duties, this research aims to determine the legal arrangements for UN special missions. It also seeks to ascertain the UN's responsibility for UN special mission participants who die while performing their duties. Normative legal research is the kind of study that is employed. The findings demonstrate how crucial it is for UN special missions to have legal guidelines when performing their duties in order to guarantee that all actions are compliant with UN policies and goals. This entails compliance with international laws like the Geneva Conventions, internal UN policies, and approval from the nations in which the mission operates. When viewed from the perspective of sending countries against participants in special UN peace missions, there is protection in the form of compensation, medical assistance, and family support. Through this arrangement, the UN can carry out humanitarian and peace missions safely and effectively, and provide protection to mission personnel. The sending nation also provides training to the soldiers, including topics such as international law, human rights, law enforcement methods, and mission guidelines. Additionally, to help them deal with the difficulties they could encounter on a peace mission, participants receive training in stress management, communication, negotiation, and conflict resolution techniques. In order for mission participants to contribute to global peace in a secure and efficient manner, it is critical that these legal provisions be upheld and monitored. When a mission member dies while performing their duties, the UN is held accountable. They are required to look into the death with great care, support the relatives of the deceased, and make sure that future missions have stronger preventive measures in place.